A Community-Based Approach to Diarrhea Recovery in Children: The Role of WASH and Family Engagement (PT. LARPA JAYA PUBLISHER, 2025)
Diarrhea in young children is a common health issue that can significantly affect a child's health status. The management of diarrhea in children requires a holistic approach, integrating medical, social, and environmental factors. This study describes the management of diarrhea in An. R, a 4-year-old child who experienced mild acute diarrhea. The interventions included hygiene education, oral rehydration therapy, the provision of low-fiber food, and active family involvement in the child's recovery. The results of the study show that the education provided, together with WASH (Water, Sanitation, and Hygiene)-based interventions, were effective in reducing diarrhea symptoms and accelerating recovery. Additionally, factors such as nutritional status, immunization, and environmental sanitation also influence the occurrence of diarrhea. This study concludes that the success of managing diarrhea in young children heavily relies on collaboration between families, healthcare providers, and public health policies. Effective management can be achieved through a community-based approach that emphasizes sanitation education and active family involvement.